University Cooperation Platform (UCP) between Christian-Albrechts-University Kiel (Germany) and Chiang Mai University (Thailand): Implementation of image-guided gynecological brachytherapy - Galalae R. (Termedia Publishing House Ltd., 2015)
Starting in 1999, the University Cooperation Platform (UCP) implemented an exchange program of researchers and clinicians/physicists between the Christian-Albrechts-University Kiel in Germany and Chiang Mai University in Thailand, to initiate a sustainable base for long-term development of image-guided brachytherapy and in general for high-technology radiotherapy in Chiang Mai. A series of UCP protocols, based constructively on each other, were performed and evaluated at intermediate term follow-up. The first protocol, addressing computed tomography (CT)-optimized brachytherapy for advanced cervical cancer (n = 17), showed a significant reduction of D2cc for the bladder and sigmoid (p < 0.001) while maintaining a very high dose in D90 high-risk clinical target volume (HR-CTV) in comparison with standard point-based planning. In addition, after a follow-up of 19 months no tumor relapse was observed. The second UCP protocol, testing the impact of magnetic resonance imaging (MRI) guidance (n = 15) in patients with cervical cancer, proved significantly smaller D2cc doses for the bladder, rectum, and sigmoid (p = 0.003, p = 0.015, and p = 0.012), and secured highly curative mean doses in D90 HR-CTV of 99.2 Gy. The acute and late toxicity was excellent without any observed grade 3 or higher morbidity. In the third protocol, the combination of image-guided brachytherapy (IGBT) and whole pelvis intensity-modulated external beam radiotherapy (WP-IMRT) (n = 15) reaffirmed the significant reduction of D2cc doses for the bladder, rectum, and sigmoid (p = 0.001 or p < 0.001) along with high equivalent dose at 2 Gy (EQD2) in the HR-CTV, and demonstrated very low acute therapy-related toxicity in absence of grade 3 morbidity. The implementation of transabdominal ultrasound (TAUS) was the focus of the fourth UCP project aiming a more generous potential use of image-guidance on long-term, and enhancing the quality of soft tissue assessment complementary to conventionally planned gynecological brachytherapy. Analyses in 29 patients revealed significantly reduced OARs doses in bladder with a total EQD2 > 80 Gy for bladder in only 17.2% versus 62.1% in conventional planning, and in rectum EQD2 > 75 Gy in 44.8% versus 79.3%, respectively. In conclusion, analyses revealed excellent results for the high-dose-rate IGBT in patients with advanced gynecological cancer both by using CT and MRI, and/or the combination with WP-IMRT. They also define MRI as gold standard for soft tissue assessment and to determine more accurately HR-CTV. The use of TAUS-guidance adds quality aspects to the "classical" conventional X-ray based planning, especially in terms of real-time measures and adequate soft tissue information, and may lower significantly the dose in OARs. The review of all UCP-results reconfirms the importance of the established program that will continue to operate with subsequent projects.